Urinary Balantidiasis with urinary tract system Tuberculosis: A rare case report (Journal of Pathology of Nepal, 2025)
Balantidium coli, a largest protozoan, is a rare zoonotic disease in humans, predominantly detected in stool examination. We are presenting a case of incidentally detected urinary balantidiasis in a patient with genitourinary tract tuberculosis, which is the first case with such presentation.